Estudos do nível de utilização de sistemas de gerenciamento de ferramentas de corte em empresas de maquinas e implementos agrícolas - Souza, Eduardo de (2011)
In the current world scenario the Agribusiness comes emerging as a growing market mainly for Brazil. In order to monitor this growth companies of machinery and agricultural implements (EMIA) are increasing every year its production capacity metal-mechanics. As the EMIA increase its production all inputs used in the manufacturing process are controlled more attentive staff. It is very important in the factories of machining a control of all the cutting tools used in manufacturing processes. Some companies in the segment automotive already use pioneer Management Systems Cutting Tools (SGFC) to improve its productivity and service the high demand of the global market. Machining enterprises directed to the Agribusiness analyzes for use of SGFC begin appear. This work aims to identify and evaluate the use of management system cutting tools in enterprises of machinery and agricultural implements in Brazil. The methodology applied used a lifting of the type survey. Through a questionnaire sent to undertakings metal-mechanical Agribusiness segment. Obtained if an outcome that presents important factors for which there is the implantation of SGFC in EMIA and factors that make the deployment of the systems of management. Note that some companies do not use management system in its totality.